Improving Critical Thinking Skills Through a Demonstration of a Water Wheel for Generating Electricity, Content for Science Lessons, Students of Grade VI SDN 3 Pakikiran - Endah Sri Haryanti; Ristiana Dyah Purwandari (UM Purwokerto Press, 2023)
The ability to think critically in science class VI students at SDN 3 Pakikiran is low, namely learning completeness is 46.16% with an average score of 53.73. The formulation of the research problem is: How to improve critical thinking skills through a demonstration of a water wheel for science power generation for class VI students at SDN 3 Pakikiran?. The research was conducted in class VI at SDN 3 Pakikiran in semester 1 of the 2022/2023 academic year. The research subjects were 13 students. The research data is descriptive quantitative with data collection techniques through written tests and observations. Based on the analysis of the data, the results of the critical thinking ability test achieved 92.31% mastery with an average score of 80.77. It was concluded that the demonstration of a water wheel for generating electricity could improve the critical thinking skills of science grade VI at SDN 3 Pakikiran.